2013
DOI: 10.5001/omj.2013.58
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Glomerular Diseases on Renal Biopsy: Data From A Single Tertiary Center In Oman

Abstract: Among the secondary glomerular diseases, lupus nephritis was the commonest condition with a female preponderance. Among the primary glomerular diseases, FSGS was the commonest. These results are consistent with global trend. IgA nephropathy is not common as the case in the Caucasian population. Vasculitis was not common and there was no report of anti-GBM disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 0 publications
4
13
2
Order By: Relevance
“…13,14,20 Among primary glomerular diseases, FSGS was the most frequent pathological lesion (27.44%) encountered in our study which is similar to data from regional Asian studies. [13][14][15] However, these results depart from those reported in other published papers which show a relatively low incidence of FSGS. 18,21 MCD was found to be more common in the younger age group (18.61±13.47 years) and it was the second most frequent pathology encountered in our study (16.01%) which is identical to other studies from India, Korea, and Japan.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…13,14,20 Among primary glomerular diseases, FSGS was the most frequent pathological lesion (27.44%) encountered in our study which is similar to data from regional Asian studies. [13][14][15] However, these results depart from those reported in other published papers which show a relatively low incidence of FSGS. 18,21 MCD was found to be more common in the younger age group (18.61±13.47 years) and it was the second most frequent pathology encountered in our study (16.01%) which is identical to other studies from India, Korea, and Japan.…”
Section: Discussioncontrasting
confidence: 98%
“…13,20 In Oman, MCD was not detected among the diagnosed renal and glomerular pathologies which can be due to the higher age group of participants (patient) involved in that study. 15 MGN was more common in the older age group of our patients (38.94±13.69 years), and it represents the third most frequent diagnosis among patients with primary glomerular diseases which is identical data to other studies. 14,16,19 In Iran, MGN was the most frequent renal pathology encountered among patients with primary glomerular diseases.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…11 The study groups defined in these comprised of a higher proportion of children and young adults(<18yrs) ,around 31.15% of total subjects.The younger group(<18yrs) included in our study was only 6.87% of the total subjects.This could have accounted for the lower incidence of MCD reported. DN was the most common SGD in this study, on contrary to other studies where LN was reported as the most prevalent SGD 3,11,20,21 . DN was seen in 14.90% of total subjects (35.03% of all SGDs),with mean age of 50.48yrs, and mean creatinine of 5.69mg/dl.…”
Section: Discussioncontrasting
confidence: 52%